Effects of Sewage Sludge Compost on Carbon, Nitrogen, Phosphorus, and Sulfur Ratios and Soil Enzyme Activities in a Long-Term Experiment - Csilla Almási; Viktória Orosz; Timea Tóth; Mostafa M. Mansour; Ibolya Demeter; István Henzsel; Zsolt Bogdányi; Tamás András Szegi; Marianna Makádi (Agronomy)
The carbon, nitrogen, phosphorus, and sulfur (CNPS) ratios of soils are known to be relatively stable parameters, characterizing different land uses. We hypothesized that the long-term application of sewage sludge compost (SSC) would not change these ratios but would increase the concentration of these elements and change the quality of organic matter (OM), as well as soil enzyme activities. Hence, soil chemical and microbiological properties were studied in a 20-year long-term experiment. The plots were grouped into five blocks and treated every third year with SSC at the rates of 0, 9, 18, or 27 t ha−1. Three plants, in a crop rotation, were tested and sown every year as follows: rye, rye with hairy vetch, and maize. The results showed that basic soil parameters (pH, OM content, E4/E6 ratio, NO3-NO2-N, AL-P2O5, and soil moisture content) were increased, along with the SSC doses in soil for the rye. Similar trends were found in CNPS concentrations, β-glucosidase, and alkaline phosphatase activities, while the acidic phosphatase activity was reduced. The C:N, C:S, and N:S ratios were not affected by the compost application. The main factors of treatment effects were plant-available phosphorus (ammonium lactate (AL)-soluble P2O5), total P, and NO3-NO2-N, based on principal component analysis. The canonical correspondent analyses revealed that phosphatase activities were affected by C:N, C:P, and N:P ratios and β-glucosidase was correlated with P forms and the E4/E6 ratio, while the soil pH strongly affected all soil enzymes. Based on the alkaline and acidic phosphatase activities, the role of microbes became more important with increasing compost doses in phosphorus mobilization. We conclude that the addition of SSC could improve soil health through increasing the pH, OM, nutrient content, and microbial activity. Also, some elemental ratios have an important role in the regulation of soil enzyme activities.